Intensity of Cultivating Radicalism Values in Kindergarten Level Integrated Islamic Schools - Nurus Shalihin; Yulia Yulia; M Yusuf; Ujang Wardi (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
This study aims to look at the intensity of radical values cultivation towards early childhood and how it implies the different variants of each Integrated Islamic School. This article uses a mixed method approach. Quantitative approach is used for data collection using lift. And a qualitative approach is used to analyze the data. There are twelve kindergartens that are used as population in this study. In each population, five teachers and seven student guardians were selected by random sampling. The study found that the level of intensity of radicalism values inculcation in Islamic Schools is at the level of fanaticism with 76.65%, coercion of will with 66.58%, hard attitude with 59.87%, and prejudice with 51.40%. It was further reported that the percentage in IISN schools was 80.25, 63.29, 62.25, and 54.25 and ISSA schools have 87.25, 64.05, 75.00, and 7.05 respectively. Meanwhile, the schools without any affiliation to any institution or organization recorded 73.05%, 72.75%, 52.75%, and 48.25% respectively. This simply shows that the radical values observed in Integrated Islamic Schools are closely related to ideological, political, and economic interests.